ANALISIS HUBUNGAN PERSEPSI MAHASISWA TENTANG MATA KULIAH HOUSEKEEPING DENGAN MOTIVASI BELAJAR DI SEKOLAH TINGGI PARIWISATA TRISAKTI JAKARTA - Taviprawati, Ervina; Sembiring, Vienna Artina (Jurnal Ilmiah Pariwisata, 2017)
Education is an important means for a nation to achieve progress. Learning is a process of behavioral change that takes place consciously and involves all students' abilities. The result of behavioral change s that occur as a result of this teaching - learning process is said to be the result of learning. This can be interpreted when a person learns a knowledge, then he has new skills about knowledge that has been learned in addition to the knowledge that has be en there. This research uses descriptive and correlational method in processing and analyzing data. The unit of analysis in this study is the students who majored in housekeeping STP Trisakti In this study the object is the students of the second semester of 2015 who studied housekeeping at STP Trisakti. Data analysis method used in this research is descriptive analysis with the intent to analyze the results of questionnaires from the relationship and the influence of student perceptions about the subject o f housekeeping with motivation to learn at Trisakti Tourism High School Jakarta. Student perception about housekeeping subjects affect the learning motivation by 49.67%. While the remaining 50.33% learning motivation is influenced by other factors.